Design failure mode effect analysis: A case study in an automotive company of model XYZ - Ahmad, Mohd Akhir; Mohd Nawi, Mohd Nasrun; Taib, Che Azlan; Mat Nor, Alias (School of Technology Management and Logistics (STML), 2019)
In globally competitive manufacturing industry, the success of new product development has become more decisive an organization’s business performance. The organization needs to plan strategies to reduce defects by implementing various quality programs (Mitra, 2016) since many organizations still encounter product quality issues involving product recall, the escalation of warranty claims costs and product failures. One way to solve these issues is to incorporate quality tools by eliminating potential defects of products at an early stage using DFMEA (Andrawus, 2008). DFMEA is extensively implemented to filter the inefficiency of new product. For example, Reid (2005) and Teng et al., (2006) showed that the use of design failure mode and effect analysis (DFMEA) in proper ways can save resources and meet customer’s demands and more recently, according to Dimas Campos et al., (2014) establish relationships between FMEA and organizational performance in Brazil automotive industry. Despite a comprehensive DFMEA was demonstrated a few decades ago, little attention has been paid to DFMEA of their effectiveness in the Malaysian automotive industry.